The impact of emotional labor on the health in the workplace: a narrative review of literature from 2013-2018 - Norah Aung; Promise Tewogbola (AIMS Press, 2019)
There is a paradigm-shift in the workplace from a production mentality to a service-oriented mentality. As a result, there is a greater need on employees to expend emotional labor in dealing with the challenges of meeting the demands of a service-oriented economy. This present study discussed the impact that expending emotional labor has on the health of employees in the workplace. Literature was retrieved from MEDLINE/PubMed, Excerpta Medica/EMBASE, Scopus and Thomson Reuters' Web of Science databases. Studies were selected if they were published between 2013 and 2018, written in English and had the terms "emotional labor" or "emotional labour" in their titles. An overview of the different effects of emotional labor on the health of employees in different sectors of the economy revealed effects ranging from burnout and fatigue to dysmenorrhea, disruptions in sleep patterns and suicidal tendencies. The effects of emotional labor on the health of members of the population who belong to the working class can be attributed to reciprocal determinism where environmental influences in the form of clients, supervisors, or organizational culture put employees in a position where they had to develop the habit of engaging emotional labor to cope with environmental stresses.